Development of Mathematical Models to Analyze the Impact of Geometric Small-Scale Building Designs on Energy Efficiency: A Case Study at Navaminda Kasatriyadhiraj Royal Air Force Academy, Muak Lek - Thanompolkrang, Sirunya; Meechowna, Sompoom; Kraychang, Witsarut; Siriteerakul, Sirikul (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This research presents a mathematical model for evaluating the internal temperature of buildings with symmetrical geometric cross-sections, including rectangles, hexagons, and octagons. It examines scenarios where the cross-sectional areas or perimeters are equal. The study focuses on the transfer of heat from the outside to the inside, with walls and indoor air as the mediums. Results are presented as contour plots that depict heat diffusion levels within the building, along with temperature distribution graphs values based on reference points. The results suggest that the internal temperature is more significantly affected by the direction of sunlight than by the type of building.